Aplicando o modelo de letramentos acadêmicos no contexto da sala de aula EMI - Ribeiro, Juliana Michelon (2023)
This work is part of the research project “Inglês como meio de instrução (EMI) na UFSM: políticas, percepções e implementação em direção à internacionalização” (HENDGES, 2018). In the context of the internationalization, EMI is often cited as one of the strategies of this process, both by researchers (BAUMVOL; SARMENTO, 2016a) and by members of the academic community, such as professors and students (DUARTE; PRETTO; HENDGES, 2018). Academic Literacies, in this context, are a theoretical-methodological approach that can contribute to the research of the modality and its broader context, internationalization, in a critical way and based on ethnography as well as in teaching actions about the modality, maintaining the critical and transformative characteristics of this area. The aim of this work is to extend Lea and Street's (1998) models of academic writing to the analysis of academic communicative practices in an EMI PPGQ course. To do so, first, a systematization of the characteristics of the three models (study skills, academic socialization and academic literacies) was developed as a basis for further analysis. Next, the universe of analysis was investigated. The profile of class participants was mapped through analysis of Lattes curricula. Data generation starts from the observation of a class in a PPGQ EMI course. Excerpts from the observed class were analyzed in two moments: first, an analysis of the rhetorical movements was carried out; then, based on the systematization of the literature on Academic Literacies and the three models of academic writing described by Lea and Street (1998). Considering the studies on rhetorical movements in the university context, it was noted that they were limited to regular academic subject classes and academic English courses. The analyzed class covered aspects of both genres for sharing certain communicative objectives. Thus, these works contribute to this study, but not exhaustively. With regard to the expansion of the Lea and Street (1998) models, it was detected that the models could be identified in the analyzed class under different levels. While in the description by Lea and Street (1998) the focus was on writing, the analyzed class covered different academic communicative practices and went beyond the written record. Therefore, the excerpts transcribed from the class were analyzed from three levels: i) linguistic level, focusing on language, especially in English, from the lexical-grammatical level to the discursive level (HALLIDAY, 1994); ii) content level, focusing on the ways that the professor could deal with the specialized content of a class in the area; and iii) classroom level, which focuses on possibilities of classroom dynamics. The three models seem to underlie the teacher's actions in the classroom, but, considering the three proposed levels, only the academic literacies model was identified in all of them.